An innovation systems approach to sustainability transitions: analysing socio-cognitive institutions in Austrian and South African cases - Van Heyningen, Jan Pieter (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.